2014
DOI: 10.1108/mip-05-2013-0074
|View full text |Cite
|
Sign up to set email alerts
|

The impact of promotional mix on profit in the B2B sector

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Some studies assess the effect of each marketing activity on product sales over time, by separating short and long term effects (Ataman, Van Heerde, & Mela, 2010;Jandaghi, Amiri, Amini, & Darani, 2011), and others investigate the dynamic effect of these activities on revenue, profitability, and value in the financial market (Feng, Morgan, & Rego, 2015;Lima & Porto, 2012;Mizik, 2014;Siddhanta & Banerjee, 2014).…”
Section: Marketing Dynamics and The Financial Performance Of Small Enmentioning
confidence: 99%
“…Some studies assess the effect of each marketing activity on product sales over time, by separating short and long term effects (Ataman, Van Heerde, & Mela, 2010;Jandaghi, Amiri, Amini, & Darani, 2011), and others investigate the dynamic effect of these activities on revenue, profitability, and value in the financial market (Feng, Morgan, & Rego, 2015;Lima & Porto, 2012;Mizik, 2014;Siddhanta & Banerjee, 2014).…”
Section: Marketing Dynamics and The Financial Performance Of Small Enmentioning
confidence: 99%
“…VAR analysis often leads to the estimation of IRFs and FEVDs which are essential parts of the VAR method. We followed the example of [ 79 , 80 ] for setting the IRFs and FEVDs for a 10-year horizon.…”
Section: Introductionmentioning
confidence: 99%
“…Promotional tools and strategies aiming to attract the public should be properly and systematically planned to ensure that marketing activities are effective and productive (Masa'deh et al, 2018). Past studies indicated the prominent role of promotion for a product, service, or idea (Qian et al, 2019;Siddhanta & Banerjee, 2014;Untari et al, 2019). Undeniably, promotion is an excellent way to market a product, service, or idea.…”
Section: Introductionmentioning
confidence: 99%